On the Validity of the Regression Discontinuity Design for Estimating Electoral Effects: New Evidence from Over 40,000 Close Races - Eggers, Andrew C.; Fowler, Anthony; Hainmueller, Jens; Hall, Andrew B.; Snyder Jr, James M. (American journal of political science, 2015)
The regression discontinuity (RD) design is a valuable tool for identifying electoral effects, but this design is only effective when relevant actors do not have precise control over election results. Several recent papers contend that such precise control is possible in large elections, pointing out that the incumbent party is more likely to win very close elections in the United States House of Representatives in recent periods. In this article, we examine whether similar patterns occur in other electoral settings, including the U.S. House in other time periods, statewide, state legislative, and mayoral races in the U.S. and national or local elections in nine other countries. No other case exhibits this pattern. We also cast doubt on suggested explanations for incumbent success in close House races. We conclude that the assumptions behind the RD design are likely to be met in a wide variety of electoral settings and offer a set of best practices for RD researchers going forward.